Hubungan Pola Asuh Orang Tua Dengan Prestasi Belajar PKN pada Murid Kelas V SD Negeri Tallang-Tallang Kecamatan Pallangga Kabupaten Gowa - Rismawati Rismawati (Universitas of Muhammadiyah Makassar, 2017)
Abstract. This study aims to determine the Relationship Pattern Parent Parenting With Learning Achievement In Students Class V State Element Tallang-Tallang Pallangga District Gowa District. This research is a correlation research with inferential statistical analysis of product moment correlation coefficient. The population in this study were all students of State Elementary School Tallang-Tallang Pallangga District Gowa Regency as many as 214 people, the sample was taken by using purposive sampling technique as much as 46 people. Data were collected through questionnaires and documentation techniques. After analyzing the data the authors found that the value of r arithmet obtained greater is 0.408 than the value of r table is 0.291 on the basis of a significant level of 5%. Thus, the hypothesis in this research is accepted.Keywords: Patterns of Parent-nursing, Achievement of PKN Learning